MENINGKATKAN KESADARAN HUKUM TERHADAP KEHIDUPAN BERMASYARAKAT UNTUK MENCAPAI KEHARMONISAN DAN KETERTIBAN DI DESA BUNTU NANNA - Zulhas`ari Mustafa; Taufan Makmur; Reski; Andi Dilla Febrianti; Nuranti (Pangulu Abdi: Jurnal Pengabdian Kepada Masyarakat, 2021)
Indonesia as a State of Law (Rechtsstaat) Not States of Power (machstaat). This statement indicates that all actions must be based on law. Community legal awareness as an embodiment of the legal culture of the community must continue to be instilled so that community compliance with the law can continue to be improved. As is known, the law is the highest rule that must be implemented by the community in carrying out social interactions, and by the authorities in carrying out state and social life, because the concepts, ideas and social ideals inherent in the law are emanations of the value system. who live in the heart of the community concerned.